2020
DOI: 10.11591/ijere.v9i3.20686
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the quality of school life and the school burnout

Abstract: School burnout has been a research subject during recent years and is a wide case among students is associated with many factors. Among these factors, school-related concepts are remarkable. Within this study, it is aimed to investigate the relationship between school quality, school burnout and school burnout. The participant group of the study consists of a total of 364 secondary school students, 181 girls and 183 boys, whose ages are in the range of 10-15, attending various secondary schools. This sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
2
4
0
4
Order By: Relevance
“…Estos espacios facilitan compartir reflexión, memorias, sentimientos, gusto y momentos que guían al acuerdo y aceptación de las desigualdades con respeto y tolerancia. Es crucial que estas actividades estén bajo observación con responsabilidad de los mayores que son parte de la sociedad de educación, como docentes, directores y padres de familia (Gündogan y Özgen, 2020).…”
Section: Bases Teóricas De La Investigaciónunclassified
“…Estos espacios facilitan compartir reflexión, memorias, sentimientos, gusto y momentos que guían al acuerdo y aceptación de las desigualdades con respeto y tolerancia. Es crucial que estas actividades estén bajo observación con responsabilidad de los mayores que son parte de la sociedad de educación, como docentes, directores y padres de familia (Gündogan y Özgen, 2020).…”
Section: Bases Teóricas De La Investigaciónunclassified
“…Adanya QSL yang baik akan membuat siswa memiliki perkembangan diri yang baik dengan merasakan kesejahteraan yang ada di dalam lingkungan sekolah, yang mana hal tersebut ditentukan berdasarkan persepsi serta pengalaman-pengalaman siswa selama berada di sekolah. Menurut Epstein QSL sebagai sebuah penilaian dari seorang individu yang dapat dipengaruhi dari dimensi-dimensi pada lingkungan sekolah yang mencakup kepuasan pada seorang individu terhadap lingkungan sekolah yang mengukur kesejahteraan individu secara umum terhadap kehidupan di sekolah, komitmen terhadap tugas sekolah, serta reaksi atau hubungan sosial antara siswa dengan guru/pendidik dan sebaliknya (Selim Gündoğan, 2020).…”
Section: Pengaruh Qsl and Burnout Terhadap Kesejahteraan Subjektifunclassified
“…Research studies in Turkey identified levels of school quality of life, while research studies in South Korea focused on the importance of traditional Confucius values. (20) , in their research the relationship between school quality of life and school burnout. School burnout has been a topic of research for the past few years and is a broad case among students that is associated with many factors.…”
Section: Related Workmentioning
confidence: 99%